New solutions in designing mechanized hump yards - Березовый, Николай Иванович (Eastern-European Journal of Enterprise Technologies, 2013)
For the reduction of investments in the construction and operational costs, associated with the breaking-up and making-up of trains on the mechanized hump yards, the new approach to the design of the plan of yard necks of classification yards was proposed. Transfer of the park brake position to the straight segments within the curved beyond the last railroad switches allows to reduce the length of the calculated path of rolling of cuts and consequently to reduce the cost of the humping track and braking of cuts. Thus, the required brake power of retarders of the drain part of the hump yard and the park brake position is reduced. New design solutions on the placement of retarders of park brake position on tracks with minimal inter-track space were developed, namely the allocation of retarders of one bunch in the general cut-off trench with the arrangement of steps in each inter-track space on both sides of the trench; the displacement of the control equipment of retarder on the inter-track space axis for compliance with the loading gauge and structure gauge, and the corresponding displacement of the high-pressure air pipelines for the switching-on of retarders